(untitled) (Research, Society and Development, 2025)
This study was carried out in a small lentic environment (Córrego Sete de Setembro Dam) in the municipality of Nanuque (MG). The objective was to evaluate the water quality of this dam by calculating the WQI (water quality index) in the months of December 2015 and June 2016, corresponding to the rainy and dry seasons, respectively. By calculating the WQI, it was observed that the dam has a poor water quality index. A high concentration of thermotolerant coliforms and phosphorus was observed during the rainy season, confirming the occurrence of domestic waste dumping in the water body that feeds the dam and that this waste alters the water quality. The results prove the fragility of establishing water quality when the polluting source is domestic sewage, reinforcing the need for adequate treatment of domestic effluent and improvement of the impacted aquatic ecosystems.